2015
DOI: 10.1155/2015/375391
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Subacute Administration of Zinc Increases CCL2, CCR2, FGF2, and IGF-1 Expression and Prevents the Long-Term Memory Loss in a Rat Model of Cerebral Hypoxia-Ischemia

Abstract: Prophylactic subacute administration of zinc decreases lipoperoxidation and cell death following a transient cerebral hypoxia-ischemia, thus suggesting neuroprotective and preconditioning effects. Chemokines and growth factors are also involved in the neuroprotective effect in hypoxia-ischemia. We explored whether zinc prevents the cerebral cortex-hippocampus injury through regulation of CCL2, CCR2, FGF2, and IGF-1 expression following a 10 min of common carotid artery occlusion (CCAO). Male rats were grouped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 81 publications
(106 reference statements)
1
23
0
Order By: Relevance
“…The facilitation of learning and improvement of cognitive development have been associated to the neuroprotective effect of zinc, which decreases free radicals produced by cerebral ischemia [ 76 ]. Our group showed similar results in the preconditioning effect of subacute zinc administration in the CCAO rat model [ 5 ]. However, the prophylactic chronic zinc administration (0.2 mg/kg of body weight/days) exerted a partial effect because there was no memory consolidation as reported previously with a higher dose of zinc [ 19 ].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The facilitation of learning and improvement of cognitive development have been associated to the neuroprotective effect of zinc, which decreases free radicals produced by cerebral ischemia [ 76 ]. Our group showed similar results in the preconditioning effect of subacute zinc administration in the CCAO rat model [ 5 ]. However, the prophylactic chronic zinc administration (0.2 mg/kg of body weight/days) exerted a partial effect because there was no memory consolidation as reported previously with a higher dose of zinc [ 19 ].…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, CCL2 also stimulates the migration of neuronal precursor cells to the damaged area [ 66 ]. We have previously reported that high levels of CCL2 by a subacute prophylactic administration of zinc are associated with a preconditioning process [ 5 ]. However, the combined treatment with zinc and selenium did not maintain the preconditioning effect of zinc but exerted the therapeutic effect of selenium in the late phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCL2 levels after ZnONP exposure either in vivo (lung) or in vitro[158,179,214]. According to Sahu et al, ZnONP promote the expression of the MCP-1 mRNA level in THP-1 cells in vitro after exposure[215].…”
mentioning
confidence: 99%